A study on the mix proportion of foamed concrete to early compressive strength development and tensile strength development / Nor Maslina Mohsan, Khalimi Johan Abd Hamid and Nurul Huda Suliman - Mohsan, Nor Maslina; Abd Hamid, Khalimi Johan; Suliman, Nurul Huda (2009)
Foamed concrete is cement-based slurry that is mechanically blended to form stable and homogeneous foam. The process can be either by mixing or by injecting. The compressive strength of foamed concrete is a function of density depends on many factors such as sand/cement ratios, water/cement ratios, curing conditions and particle size distribution of sand. The scope of this paper is to study the effect of density, mix proportion of cement-sand ratio and admixtures to compressive strength of foamed concrete at early age and the tensile strength at age 28 days. Three types of concrete are used; normal foamed concrete, foamed concrete with Glenium C380 and foamed concrete with Calcium Nitrate. Results showed that the early compressive strength increases with increase in density for all types of concrete used. The effect of mix proportions of cement-sand ratio showed significant early compressive strength increases with increase in cement content. Mix 2: 1 (for normal foamed concrete) shows highest early compressive strength to compare with other mix. It is also observed that, foamed concrete with admixtures (Glenium C380 and Calcium Nitrate) gives higher early compressive strength compared to normal foamed concrete. Results concluded that there has significant effect on tensile strength of 1: 1 mix foamed concrete added with surfactant. The tensile strength value reduced with more percentage of surfactant added to the mix.